2016
DOI: 10.1177/0021998316644849
|View full text |Cite
|
Sign up to set email alerts
|

An optical method for measuring surface roughness of machined carbon fibre-reinforced plastic composites

Abstract: Characterization of the damage induced by machining of fibre-reinforced composites is usually performed by measuring surface roughness. Contact-based surface profilometers are the most used equipment in industry; however, it has been found that there are performance limitations which may result when used to measure machined heterogeneous composite surfaces. In this research, surface roughness is characterised using a commercial non-contact optical method, and compared with a conventional stylus profilometer. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…[1][2][3][4][5] Cutting parameters and uncut chip thickness have additionally been shown to have a critical effect on machining induced surface quality and pitting magnitude. [6][7][8] Chen et al 9 have compiled a thorough analysis of the different types of cutting mechanism for the 0°, 45°, 90°and 135°fibre orientations, using micro textured tools in a composite milling process, and shown how fibre orientation will influence the machined surface quality. Specifically, in composite machining, it has been shown that ply orientation will significantly dictate the machined surface topography, cutting mechanism and defect types.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Cutting parameters and uncut chip thickness have additionally been shown to have a critical effect on machining induced surface quality and pitting magnitude. [6][7][8] Chen et al 9 have compiled a thorough analysis of the different types of cutting mechanism for the 0°, 45°, 90°and 135°fibre orientations, using micro textured tools in a composite milling process, and shown how fibre orientation will influence the machined surface quality. Specifically, in composite machining, it has been shown that ply orientation will significantly dictate the machined surface topography, cutting mechanism and defect types.…”
Section: Introductionmentioning
confidence: 99%
“…This aims to determine best results of the machine according to the temperature tested. Surface roughness test for plastic composites by applying an optical method was measured [21]. Furthermore, plastic pipes that were used for irrigation were calculated experimentally using internal surface roughness test [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authors proved the surface roughness increased with machining distance generally following a steady trend. They also reported that diamond coated tool with multiple cutting teeth or also known as burrs tool was able to produce a good quality surface although at high feed rate, V f in comparison with polycrystalline diamond (PCD) tool [17,18]. Souhir Gara and Oleg Tsoumarev performed a series of comparison study on a few different micro-grain of burr tool which categorized into fine, medium and coarse type in slotting CFRP material.…”
Section: Introductionmentioning
confidence: 99%